Impact of Pharmacists' Intervention on the knowledge of HIV infected patients in a public sector hospital of KwaZulu-Natal - Saloshini Govender; Tonya Esterhuizen; Panjasaram Naidoo (AOSIS, 2011)
Background: The study site started its roll-out of the human immunodeficiency virus (HIV) prevention of mother-to-child transmission in 2006. All patients were counselled by trained counsellors, before seeing a doctor. At the pharmacy the medicines were collected with no intense counselling by a pharmacist as the patients would have visited the trained counsellors first. Subsequently it was found that there were many queries regarding HIV and acquired immune deficiency syndrome (AIDS). Thus a dedicated antiretroviral pharmacy managed by a pharmacist was established to support the counsellors. Objectives: The objective of the study was to assess the impact of a pharmacist intervention on the knowledge gained by HIV and AIDS patients with regard to the disease, antiretroviral drug use (i.e. how the medication is taken, its storage and the management of side effects) as well as adherence to treatment. Method: This study was undertaken at a public sector hospital using anonymous structured questionnaires and was divided into three phases: pre-intervention, intervention and postintervention phases. After obtaining patient consent the questionnaires were administered during the first phase. A month later all patients who visited the pharmacy were counselled intensely on various aspects of HIV and antiretroviral medication. Thereafter patients who participated in Phase 1 were asked to participate in the second phase. After obtaining their consent again, the same questionnaire was administered to them. Quantitative variables were compared between pre-intervention and post-intervention stages by using paired t-tests or Wilcoxon signed ranks tests. Categorical variables were compared using McNemar's Chi-square test (Binary) or McNemar-Bowker test for ordinal variables. Results: Overall the mean knowledge score on the disease itself had increased significantly (s.d. 6.6%), (p < 0.01), after the pharmacists' intervention (pre-intervention was 82.1% and post-intervention was 86.3%). A significant improvement was noted in the overall knowledge score with regard to medicine taking and storage (p < 0.05) and the management of the side effects. There was a non-significant difference between the adherence in pre-intervention and in post-intervention (p = 0.077). Conclusion: Pharmacists' intervention had a positive impact on HIV infected patients' HIV and AIDS knowledge on both the disease and on the antiretroviral drug use and storage.